Sustainable justice and the community - Leonard, Liam; Kenny, Paula (Advances in ecopolitics ;, 2010)
Sustainable Justice and the Community is an attempt to locate justice in a workable and sustainable way within the community, introducing Sustainable Justice as a key concept for the coming century. This volume is a critical examination of three key concepts which need to be understood for the management of todays flexible and fluid society, namely Sustainability, Justice and Community. Within this study, we seek to explore both through an analysis built from their original philosophical understandings, through to their contemporary usage and application, ultimately developing new understandings through a combination of the essential thematic notions underpinning these salient concepts.